230k views
4 votes
If f(3x)=f(3) + f(x) then show that f(1)-f(3)-f(9) -f(27) = f (81).​

User Antares
by
4.9k points

1 Answer

4 votes

The claim is wrong, or your question is incorrectly entered.


x=1 \implies f(3) = f(3) + f(1) \implies f(1) = 0


x=3 \implies f(9) = f(3) + f(3) = 2f(3)


x=9 \implies f(27) = f(3) + f(9) = 3 f(3)


x=27 \implies f(81) = f(3) + f(27) = 4f(3)

Then


f(1) - f(3) - f(9) - f(27) = 0 - f(3) - 2f(3) - 3f(3) = -6f(3) \\eq 4f(3) = f(81)

at least if
f(3)\\eq0.

User Candie
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.